Quantum-Chemical Research of Fluoro Containing Hydrocarbons, That Have Fire Extinguishing Effect - Kukueva, V.V. (Physics and Chemistry of Solid State, 2015)
Through quantum-chemical calculations, a study was conducted to find the probable products of the destruction of molecules of extinguishing agents. The formation of atomic fluorine and trifluoromethane radical has been shown to contribute to the retardation of elementary reactions in the flame. It has been shown that active inhibitory components are more easily dissociated from the silica surface than in the case of bulk molecules.